PERBEDAAN PENGETAHUAN DAN SIKAP IBU TENTANG ASI EKSKLUSIF SEBELUM DAN SESUDAH PENYULUHAN - Girsang, Vierto Irennius; Tasiah, Tasiah; Purba, Ivan Elisabeth (Jurnal Reproductive Health, 2022)
Basic health research (Riskesdas) in the year 2013 found 30.2% 0-6 month baby gets BREAST MILK alone in the last 24 hours. The numbers are still relatively low, whereas BREAST MILK and breastfeeding is very beneficial for the mother and her baby. The constraints of the mother in breast-feeding there are 2 factors i.e. internal factors and external factors. Internal factors namely the mother's lack of knowledge about lactation management and external factors i.e. BREAST MILK has not come out on the first day so that mothers think need to add milk formula. The mother did not know the benefits of BREAST MILK for mothers and babies and not knowing that it is the Exclusive breast feeding BREAST MILK only up to the age of 6 months baby. For it is done the research that aims to analyse the comparison of the knowledge and attitudes of mothers before and after illumination of diDesa Siatas Exclusive BREAST MILK and fold in Kajang. This research is a research quasi experimental design study one group pretest-posttest. This research population is mothers who have babies age 6 months at the time of data retrieval is performed in the village and the village of Kajang Siatas Folding with the amount of 45 people and is entirely made of samples and data were analyzed with paired t-test test. The results of the research there is a difference in the average Maternal Knowledge before and after the Extension Of Exclusive breast milk (0-6) in the village of Folding And Siatas Kajang with p value = 0.001 (p < 0.05), and there is a difference Score the attitude of mothers before and after Extension About Exclusive breast milk (0-6) in the village of Folding And Siatas Kajang with p value = 0.001 (p < 0.05). Expected for the respondents to increase knowledge about BREAST MILK by following the guidance in the ASI counseling posyandu and lactation classes.